Validation of miR-20a as a Tumor Suppressor Gene in Liver Carcinoma Using Hepatocyte-Specific Hyperactive piggyBac Transposons - Jaitip Tipanee; Mario Di Matteo; Warut Tulalamba; Ermira Samara-Kuko; Jiri Keirsse; Jo A. Van Ginderachter; Marinee Khim Chuah; Thierry VandenDriessche (Elsevier, 2020)
We established a semi-high-throughput in vivo screening platform using hyperactive piggyBac (hyPB) transposons (designated as PB-miR) to identify microRNAs (miRs) that inhibit hepatocellular carcinoma (HCC) development in vivo, following miR overexpression in hepatocytes. PB-miRs encoding six different miRs from the miR-17-92 cluster and nine miRs from outside this cluster were transfected into mouse livers that were chemically induced to develop HCC. In this slow-onset HCC model, miR-20a significantly inhibited HCC. Next, we developed a more aggressive HCC model by overexpression of oncogenic Harvey rat sarcoma viral oncogene homolog (HRASG12V) and c-MYC oncogenes that accelerated HCC development after only 6 weeks. The tumor suppressor effect of miR-20a could be demonstrated even in this rapid-onset HRASG12V/c-MYC HCC model, consistent with significantly prolonged survival and decreased HCC tumor burden. Comprehensive RNA expression profiling of 95 selected genes typically associated with HCC development revealed differentially expressed genes and functional pathways that were associated with miR-20a-mediated HCC suppression. To our knowledge, this is the first study establishing a direct causal relationship between miR-20a overexpression and liver cancer inhibition in vivo. Moreover, these results demonstrate that hepatocyte-specific hyPB transposons are an efficient platform to screen and identify miRs that affect overall survival and HCC tumor regression. Keywords: miR-20a, transposon, gene therapy, piggyBac, oncogene, hepatocellular carcinoma, HRAS, c-MYC, non-viral vector, miR-17-92